2016
DOI: 10.2106/jbjs.14.00872
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Nonunions of Hindfoot and Ankle Fusions

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…* References 1,5,8,10,21,23,25,27,28,30,33,38,39. modifying their workplace requirements even existed. Similar studies 12,20,41 describing patients suffering from back pain found that return to work can be increased remarkably when the employer can offer work that is physically less demanding.…”
Section: Discussionmentioning
confidence: 99%
“…* References 1,5,8,10,21,23,25,27,28,30,33,38,39. modifying their workplace requirements even existed. Similar studies 12,20,41 describing patients suffering from back pain found that return to work can be increased remarkably when the employer can offer work that is physically less demanding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are only two case series found that describe the use of DBM in foot or ankle arthrodesis. 55 , 56 Foot and ankle arthrodesis are known to have a high nonunion rate leading to poor functional outcomes, 72 however, whether DBM is capable of reducing the nonunion rate, similar to autologous bone grafts, 73 remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Nonunion has been reported in approximately 10% of patients, heightened among subpopulations that include smokers and patients with poorly controlled diabetes or neuropathy. 5 Studies have also reported high rates of eventual adjacent joint arthritis, presumably due to the increased stress inherent to the loss of a motion segment, although few of these patients seem to require further intervention. 3 Furthermore, small case studies have reported tibial stress fracture following ankle arthrodesis, presumably due to a stress transfer to the distal tibia.…”
Section: Introductionmentioning
confidence: 99%